Gender differences in hypertension awareness, antihypertensive use and blood pressure control in Nepalese adults: Findings from a nationwide cross-sectional survey - Gupta, Rajat Das; Haider, Shams Shabab; Sutradhar, Ipsita; Hasan, Mehedi; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (Cambridge University Press, 2022)
This article was published in Journal of Biosocial Science [ © Cambridge University Press 2019] and the definite version is available at: https://doi.org/10.1017/S0021932019000531. The Journal's website is at: https://www.cambridge.org/core/journals/journal-of-biosocial-science/article/gender-differences-in-hypertension-awareness-antihypertensive-use-and-blood-pressure-control-in-nepalese-adults-findings-from-a-nationwide-crosssectional-survey/70F7B899C301B33C9BA4E9AF5D722240